Ipilimumab in the real world: the UK expanded access programme experience in previously treated advanced melanoma patients. Issue 5 (October 2015) - Ahmad, Saif S.; Qian, Wendi; Ellis, Sarah; Mason, Elaine; Khattak, Muhammad A.; Gupta, Avinash; Shaw, Heather; Quinton, Amy; Kovarikova, Jarmila; Thillai, Kiruthikah; Rao, Ankit; Board, Ruth; et al.
Abstract : Before licensing, ipilimumab was first made available to previously treated advanced melanoma patients through an expanded access programme (EAP) across Europe. We interrogated data from UK EAP patients to inform future clinical practice. Clinicians registered in the UK EAP provided anonymized patient data using a prespecified variable fields datasheet. Data collected were baseline patient characteristics, treatment delivered, toxicity, response, progression-free survival and overall survival (OS). Data were received for 193 previously treated metastatic melanoma patients, whose primary sites were cutaneous (82%), uveal (8%), mucosal (2%), acral (3%) or unknown (5%). At baseline, 88% of patients had a performance status (PS) of 0–1 and 20% had brain metastases. Of the patients, 53% received all four planned cycles of ipilimumab; the most common reason for stopping early was disease progression, including death from melanoma. Toxicity was recorded for 171 patients, 30% of whom experienced an adverse event of grade 3 or higher, the most common being diarrhoea (13%) and fatigue (9%). At a median follow-up of 23 months, the median progression-free survival and OS were 2.8 and 6.1 months, respectively; the 1-year and 2-year OS rates were 31 and 14.8%, respectively. The 2-year OS was significantly lower for patients with poorer PS ( P <0.0001), low albumin concentrations ( P <0.0001), the presence of brain metastases ( P =0.007) and lactate dehydrogenase levels more than two times the upper limit of normal ( P <0.0001) at baseline. These baseline characteristics are negative predictors of benefit from ipilimumab and should be taken into consideration before prescription.